2007
DOI: 10.1634/stemcells.2007-0321
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Manipulated Human Embryonic Stem Cell-Derived Dendritic Cells with Immune Regulatory Function

Abstract: STEM CELLS 2007;25:2720 -2729 Disclosure of potential conflicts of interest is found at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…For these purposes, administration of genetically modified DCs with enhanced immune-regulatory functions may be a promising strategy. Using directed differentiation of embryonic stem cells or induced pluripotent stem cells into DCs, we have developed efficient methods for genetically engineering mouse and human DCs (25,36,37). Among the molecules implicated in immune-regulatory functions, we found that TRAIL was the were stimulated with plate-bound anti-CD3 (3 mg/ml) and anti-CD28 mAb (3 mg/ml) and human IL-2 (20 U/ml) for 72 h. Then, mDR5, mDc-TRAIL-R1, and mDcTRAIL-R2 on each T cell subset were analyzed by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…For these purposes, administration of genetically modified DCs with enhanced immune-regulatory functions may be a promising strategy. Using directed differentiation of embryonic stem cells or induced pluripotent stem cells into DCs, we have developed efficient methods for genetically engineering mouse and human DCs (25,36,37). Among the molecules implicated in immune-regulatory functions, we found that TRAIL was the were stimulated with plate-bound anti-CD3 (3 mg/ml) and anti-CD28 mAb (3 mg/ml) and human IL-2 (20 U/ml) for 72 h. Then, mDR5, mDc-TRAIL-R1, and mDcTRAIL-R2 on each T cell subset were analyzed by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have previously established methods to generate APC or DCs from mouse [1,2] and human [3][4][5] embryonic stem (ES) cells (ES-DCs). Genetic engineering of ES-DCs can readily be done by the introduction of transgenes into undifferentiated ES cells and subsequent differentiation of the ES cell clones into ES-DCs.…”
Section: Introductionmentioning
confidence: 99%
“…Considering future clinical application of ES-DC, we also tried to generate ES-DC from human ES cells [12]. Based on experience in the generation of DC from mouse ES cells and also based on the findings in a preliminary study using cynomolgus monkey ES cells [18], feeder cell-co-culture method was adopted for the generation of DC from human ES cells, instead of the EB based method.…”
Section: Generation Of Human Es-dc Based On Op9-co-culturementioning
confidence: 99%
“…KhES-3 differentiation was similar to KhES-1 except that KhES-3 differentiated slightly more quickly than KhES-1, and a first step culture of 14-15 days was sufficient for the differentiation of KhES-3. Generation of ES-DC from nonhuman primate, cynomolgus monkey, ES cells was also achieved by this method [12].…”
Section: Generation Of Human Es-dc Based On Op9-co-culturementioning
confidence: 99%
See 1 more Smart Citation